The Effect Of Student Active Learning Group To Group Exchange Type On Student Learning Outcomes At Mts Al Washliyah Sigambal - Nadila, Wita Ferwati, Erlia Utami Panjaitan (STAI Syaichona Moh. Cholil Bangkalan, 2025)
This study aims to analyze the effect of the Student Active Learning (SAL) learning model of the Group to Group Exchange type on student learning outcomes at MTs Al Washliyah Sigambal. The research method used was a quasi-experiment with a pretest-posttest control group design. The research sample consisted of two classes, namely the experimental class (VII-5) which was taught using the Group to Group Exchange model and the control class (VII-4) which used conventional methods. Learning outcome data were collected through pre-test and post-test tests as well as observations during the learning process. The results showed that there was a significant difference between student learning outcomes in the experimental class and the control class. The average pre-test score in the experimental class was 58.4, increasing to 82.6 in the post-test. Meanwhile, the average pre-test score in the control class was 57.8, with an increase in the post-test to 72.3. The t-test showed that the t-count value of 3.87 was greater than the t-table at a significance level of 0.05, which means that the Group to Group Exchange model had a significant effect on improving student learning outcomes.